Variability in susceptibility to simulated sunlight of conidia among isolates of entomopathogenic hyphomycetes - Fargues, J.; Goettel, M.S.; Smits, N.; Ouédraogo, A.; Vidal, C.; Lacey, L.A.; Lomer, C.J.; Rougier, M. (Springer, 1996)
The influence of simulated sunlight on survival of conidia of 4 species of entomopathogenic Hyphomycetes was investigated. Conidia from 65 isolates ofBeauveria bassiana, 23 ofMetarhizium anisopliae, 14 of Metarhizium flavoviride and 33 isolates of Paecilomycesfumosoroseus were irradiated by artificial sunlight (295 to 1,100 nm at an ultraviolet-B irradiance of 0.3 W m -2) for 0, 1, 2, 4 and 8 h. Survival was estimated by comparing the number of colony forming units (CFU) produced by conidia exposed to irradiation to the number of CFUs produced by an unexposed control. Survival decreased with increased exposure to simulated sunlight; exposure for 2 h or more was detrimental to all isolates tested. Overall, isolates ofM. flavoviride were the most resistant to irradiation followed by B. bassiana and M. anisopliae. Conidia of P. fumosoroseus were most susceptible. In addition to the large interspecies differences in susceptibility to irradiation, there was also an intraspecies variation indicating that strain selection to irradiation tolerance may be important in the development of microbial control agents where increased persistence in an insolated environment is desirable.